Gerakan Peduli Stunting Di Desa Malutu Kecamatan Padang Batung Hulu Sungai Selatan - Herda Ariyani; Ridha Millati; Annisa; Anisa Herawati Sagala; Ananda Aulia Futra; Dewi Suci Hartini; Laila Fatmawati; Muhammad Dendi Firdaus Pry; Revita Melinda; Windatamara; Widharto Ali; Jamaludin Fahmi; Rima Maulina; Agil Adieb Prianto (Publikasi Inspirasi Indonesia, 2025)
Stunting and wasting are chronic nutritional problems that affect children's growth and development, particularly in rural areas. The village of Malutu Hulu Sungai Selatan has high prevalence rates of stunting and wasting, necessitating special efforts to address these issues. The Sik Asik movement (Sekumpulan Ibu Cerdas di Kelas ASI Eksklusif, or Group of Smart Mothers in Exclusive Breastfeeding Classes) was introduced as a community intervention strategy to improve the health of toddlers. This program involves educating mothers through exclusive breastfeeding classes, distributing milk to toddlers experiencing stunting and wasting, and using Smart Chart as a tool for monitoring and evaluating child development. The study aims to evaluate the effectiveness of the Sik Asik movement in reducing stunting and wasting rates in the village of Malutu. The research results show an increase in mothers' knowledge about the importance of exclusive breastfeeding and balanced nutrition, as well as a decrease in the prevalence of stunting and wasting in the intervention group. This movement has proven effective in raising awareness and community participation in stunting prevention efforts and can be replicated in other areas with similar issues.